Evaluasi Resilience dalam Budaya Keselamatan Organisasi: Studi Kasus di Situs Tambang Batubara - Iqmalia, Bella Naziel; Djunaidi, Zulkifli (FORIKES, 2025)
The high operational risks in the coal mining sector, including repeated work accidents, emphasize the urgency of implementing a resilient and adaptive safety culture. This study aimed to evaluate the implementation of Resilience Safety Culture (RSC) at PT. X. This study is a descriptive quantitative study. The subjects of the study were 300 employees selected using stratified random sampling techniques. Related data were collected by filling out a structured questionnaire based on James Reason's safety culture framework and Erik Hollnagel's Resilience Engineering principles. The collected data were analyzed descriptively and then presented categorically. The results of the study indicated that PT. X excels in the learning culture dimension through continuous training and incident investigation, but is still weak in response capabilities due to bureaucratic constraints and the less than optimal implementation of Stop Work Authority (SWA). Furthermore, it was concluded that PT. X needs to strengthen worker autonomy in emergency situations, simplify reporting flows, and prioritize safety over production to create a more resilient and adaptive safety system.Keywords: resilience engineering; safety culture; resilience safety culture; mining industry ABSTRAK Tingginya risiko operasional di sektor tambang batubara, termasuk kecelakaan kerja yang berulang, menekankan urgensi penerapan budaya keselamatan yang tangguh dan adaptif. Penelitian ini bertujuan mengevaluasi penerapan Resilience Safety Culture (RSC) di PT. X. Penelitian ini merupakan studi kuantitatif deskriptif. Subyek penelitian adalah 300 karyawan yang dipilih dengan teknik stratified random sampling. Data terkait dikumpulkan melalui pengisian kuesioner terstruktur berdasarkan kerangka budaya keselamatan James Reason dan prinsip Resilience Engineering Erik Hollnagel. Data yang telah terkumpul dianalisis secara deskriptif lalu disajikan secara kategorik. Hasil penelitian menunjukkan bahwa PT. X unggul pada dimensi learning culture melalui pelatihan berkelanjutan dan investigasi insiden, namun masih lemah dalam kemampuan respond akibat kendala birokrasi dan implementasi Stop Work Authority (SWA) yang belum optimal. Selanjutnya disimpulkan bahwa PT. X membutuhkan penguatan otonomi pekerja dalam situasi darurat, penyederhanaan alur pelaporan, dan prioritas keselamatan di atas produksi untuk menciptakan sistem keselamatan yang lebih tangguh dan adaptif.Kata kunci: resilience engineering; budaya keselamatan; resilience safety culture; industri pertambangan